Genome-Wide Analysis Reveals that PhoP Regulates Pathogenicity in Riemerella anatipestifer - Yang Zhang; Ying Wang; Yanhao Zhang; Xiangchao Jia; Chenxi Li; Zutao Zhou; Sishun Hu; Zili Li (Microbiology Spectrum, 2022)
ABSTRACT Duck infectious serositis, also known as Riemerella anatipestifer disease, infects domestic ducks, geese, and turkeys and wild birds. However, the regulatory mechanism of its pathogenicity remains unclear. The PhoPR two-component system (TCS) was first reported in Gram-negative bacteria in our previous research and was demonstrated to be involved in virulence and gene expression. Here, DNA affinity purification sequencing (DAP-seq) was applied to further explore the regulation of PhoPR in relation to pathogenicity in R. anatipestifer. A conserved motif was identified upstream of 583 candidate target genes which were directly regulated by PhoP. To further confirm the genes which are regulated by PhoR and PhoP, single-gene-deletion strains were constructed. The results of transcriptome analysis using next-generation RNA sequencing showed 136 differentially expressed genes (DEGs) between the ΔphoP strain and the wild type (WT) and 183 DEGs between the ΔphoR strain and the WT. The candidate target genes of PhoP were further identified by combining transcriptome analysis and DAP-seq, which revealed that the main direct regulons of PhoP are located on the membrane and PhoP is involved in regulating aerotolerance. Using the in vivo duck model, the pathogenicity of ΔphoP and ΔphoR mutants was found to be significantly lower than that of the WT. Together, our findings provide insight into the direct regulation of PhoP and suggest that phoPR is essential for the pathogenicity of R. anatipestifer. The gene deletion strains are expected to be candidate live vaccine strains of R. anatipestifer which can be used as ideal genetic engineering vector strains for the expression of foreign antigens. IMPORTANCE Riemerella anatipestifer is a significant pathogen with high mortality in the poultry industry that causes acute septicemia and infectious polyserositis in ducks, chickens, geese, and other avian species. Previously, we characterized the two-component system encoded by phoPR and found that R. anatipestifer almost completely lost its pathogenicity for ducklings when phoPR was deleted. However, the mechanism of PhoPR regulation of virulence in R. anatipestifer had not been deeply explored. In this study, we utilized DAP-seq to explore the DNA-binding sites of PhoP as a response regulator in the global genome. Furthermore, phoP and phoR were deleted separately, and transcriptomics analysis of the corresponding gene deletion strains was performed. We identified a series of directly regulated genes of the PhoPR two-component system. The duckling model showed that both PhoP and PhoR are essential virulence-related factors in R. anatipestifer.